PERANCANGAN CREATIVE HUB DI KOTA PONTIANAK - Kurniawan, Kurniawan; Nurhamsyah, Muhammad; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2024)
The creative industry in Pontianak City is actually quite developed, especially in the culinary, fashion, and craft sub-sectors. However, the lack of availability of creative ecosystems as well as limited space and equipment for creative actors who have ideas but do not have the capital have caused the creative industry to be unable to develop rapidly. Therefore, it is necessary to have a creative hub that functions as a place to gather, interact, collaborate, innovate, and introduce products for creative actors. In addition, this creative hub is also a forum to improve the quality of community human resources through educational events and trainings or workshops that are very useful as a provision to navigate the world of work. The design of a creative hub in Pontianak City combines three creative hub concepts, namely creative space, makerspace, and coworking space with a Contemporary Architecture approach which is expected to be able to be a solution to various design problems considering the function of the building in addition to providing a decent space, it also demands design trends that reflect the creative industry, namely always innovative and up to date.